(untitled) (Journal of the College of Basic Education, 2022)
Through our review of a number of references, we concluded that evaluation is a multi-dimensional process with integrated elements, and it is far from being a mere “number” that we reveal to the learner’s papers in a bit of abstraction sometimes, and a lot of impressionism at other times. The student is the basic element of the education system and no two people can disagree about his position in it, as it is said that the student is the center of the teaching-learning process, and this means that the student’s failure to learn leads to the failure of the teaching process. This research is of particular importance in that it highlights the evaluation It is the cornerstone of the educational process, and one of the objectives of this research is to clarify the positive role of evaluation while identifying it in terms of its concept, importance, functions, characteristics, types, and relationship with the curriculum, and this confirms that evaluation is an important and arduous process in that one requires a good training for everyone who is Responsible for this process in order to be able to monitor all areas and aspects affected by this process. The research included two sections, the first is the concept of evaluation, the importance of evaluation, functions, and characteristics, while the second topic included the types of evaluation, its relationship to the curriculum, and evaluation methods.